Electromyographic Characteristics of a Single Motion Shoulder Exercise: A Pilot Study Investigating a Novel Shoulder Exercise - Michael J Henehan; Tamar Brand-Perez; Jeffrey C Peng; Masaaki Tsuruike (International Journal of Sports Physical Therapy)
# Background